Adsorption of perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) by aluminum-based drinking water treatment residuals - Zhang, Zhiming; Sarkar, Dibyendu; Datta, Rupali; Deng, Yang (Journal of hazardous materials letters, 2021)
[Display omitted] •Aluminum-based water treatment residuals can irreversibly adsorb PFOA and PFOS.•PFOS adsorption on the residuals was greater than PFOA adsorption.•PFOA and PFOS adsorption was pH-dependent; adsorption was higher at lower pH.•Repurposing an industrial waste is a sustainable option for PFOA/PFAS treatment. Per- and polyfluoroalkyl substances (PFAS) represent a family of emerging persistent organic pollutants. Cost-effective remediation of PFAS contamination via chemical or biochemical degradation is challenging due to their extremely high stability. This study reports the removal of two representative PFAS species, perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), from water by adsorption using aluminum-based water treatment residuals (Al-WTR), a non-hazardous waste generated during the process of drinking water treatment by alum salts. Rapid adsorption of PFOA and PFOS onto Al-WTR followed a pseudo 2nd order kinetic pattern. Lower pH facilitated the adsorption process with a faster adsorption rate and greater adsorption capacity. At pH 3.0 and an initial concentration of 1.0 mg/L, 97.4 % of PFOA and 99.5 % of PFOS were adsorbed onto Al-WTR. Adsorption isotherm modeling showed that the maximum adsorption capacities of PFOA and PFOS on Al-WTR at pH 3.0 were 0.232 and 0.316 mg/g, respectively. Desorption tests indicated that the adsorption by Al-WTR was irreversible, making Al-WTR an excellent candidate for treating PFOA and PFOS in solution. The highly encouraging results of this preliminary study indicate that Al-WTR may be a promising, viable, and cost-effective PFOA/PFOS treatment option for water reuse, industrial wastewater treatment, and groundwater remediation.